Surgery for Pancreatic Cancer after neoadjuvant treatment. Issue 6 (10th September 2018) - Hackert, Thilo
Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains to be a therapeutic challenge as only 15%‐20% of all patients present with resectable tumor stages by the time of diagnosis. In the remaining patients, either local tumor extension or systemic spread are obstacles for a surgical therapy as the only chance for long‐term survival. With regard to local tumor extension, PDAC has been classified as resectable, borderline‐resectable (BR) or locally advanced (LA). While there is currently no evidence for neoadjuvant therapy in resectable PDAC, this issue remains controversial in BR‐PDAC. In the case of venous tumor involvement, guidelines mostly recommend upfront resection, when technically possible; whereas arterial involvement is regarded as an indication for chemotherapy or chemoradiotherapy first. Furthermore, in locally advanced PDAC, neoadjuvant treatment approaches have recently resulted in high rates of secondary resection, thus allowing "conversion" surgery in an otherwise palliative treatment situation. The present review gives an overview on the current literature of treatment concepts in these situations and additionally focuses of evaluation of resectability after neoadjuvant therapy as well as technical aspects in this specific situation.